Self‐Powered Smart Gloves Based on Triboelectric Nanogenerators. Issue 10 (6th September 2022) - Shen, Sophia; Xiao, Xiao; Yin, Junyi; Xiao, Xiao; Chen, Jun
Abstract: The hands are used in all facets of daily life, from simple tasks such as grasping and holding to complex tasks such as communication and using technology. Finding a way to not only monitor hand movements and gestures but also to integrate that data with technology is thus a worthwhile task. Gesture recognition is particularly important for those who rely on sign language to communicate, but the limitations of current vision‐based and sensor‐based methods, including lack of portability, bulkiness, low sensitivity, highly expensive, and need for external power sources, among many others, make them impractical for daily use. To resolve these issues, smart gloves can be created using a triboelectric nanogenerator (TENG), a self‐powered technology that functions based on the triboelectric effect and electrostatic induction and is also cheap to manufacture, small in size, lightweight, and highly flexible in terms of materials and design. In this review, an overview of the existing self‐powered smart gloves will be provided based on TENGs, both for gesture recognition and human‐machine interface, concluding with a discussion on the future outlook of these devices. Abstract : Hands are ubiquitous in daily life. Thus, having a method to monitor hand movements is a worthwhile task and can be done in a self‐powered manner using triboelectric nanogenerators (TENGs). This review covers self‐powered gloves based on TENGs for gesture recognition, sign language translation, and human‐machine interface, concluding with a future outlook on such devices.